La Ode Muhammad Idrus Qaimuddin Sastrawan Sufi Ternama di Buton Abad XIX - La Niampe (Humaniora, 2010)
This article talk about the characterization of La Ode Muhammad Idrus Qaimuddin as a popular mystical in Buton in XIX century. Among the mystical characters at his period, he known as a productive writer. His works in mysticism side was written in some languages (Wolio language, Malay, and Arabic). On of his popular poem entitled "Bula Malino" its content is about seeing which directed to him self. According to him, loving and teaching him self is a main need in the human life, so he clarified through his poem motuyaapa kaasina miya yitu, yinda molawana kaasimu yikaromu, moo sarowu guru Bemo yadariko yinda molawana yoda-yadari karomu. However people love us, it is still better loving ourselves, even though a thousand teachers who teach us, it is better we teach ourselves.